PERAN MEDIASI CAPAIAN FINANSIAL: PRAKTEK MANAJEMEN KEUANGAN DAN KEPUASAN FINANSIAL PEDAGANG BATIK DAN SOUVENIR DI PASAR BERINGHARJO YOGYAKARTA - Risal Rinofah; Pristin Prima Sari (Jurnal Kewirausahaan dan Bisnis, 2019)
This study aims to investigate the mediation role of financial experience on the link between financial management practice and financial satisfaction of Small Business Enterprise (SME) in Beringharjo Market in Yogyakarta. This study uses primary data and random sampling. This Study uses questionairre with likert scale. This study collects data to respondent in Beringharjo Market of Yogyakarta Special Region. The result of this study is financial experience can be mediator in the link between financial management practice and financial satisfaction. This study can be used to campaign financial management practice to small busniess entreprise (SME), to develop small business entreprise (SME), to make decision in business especially small business entreprise (SME). Keyword : Financial management practice, financial experience, financial satisfaction, SME, Beringharjo Market